Collaborative curricular (re)construction - Tracking faculty and student learning impacts and outcomes five years later - Duda, Gintaras Kazimieras; Danielson, Mary Ann (International Journal for Students as Partners, 2018)
The Collaborative Curricular (re)Construction, or C3, was an initiative at Creighton University that paired faculty (academics) and students in a process of backward course design, in two cohorts, in the 2013/14 and 2014/15 academic years. Faculty/student pairs worked over the span of a year to redesign a course within their discipline; courses ranged from theory-, skill-, and laboratory-based courses. The study investigated four primary questions: (1) Was C3 an effective tool for faculty development? (2) Did students emerge from the C3 experience changed as learners? (3) Did the course revisions result in increased student learning in subsequent course offerings? (4) Did the effects of the C3 workgroup affect curriculum as well as the culture within the program or department? Previous work has described the immediate impact to faculty and student; here, however, findings include the long-term impact on faculty and on student learning in the redesigned courses. Results conclude that even a brief faculty/student collaborative redesign experience has lasting impacts on student learning and, in several cases, on program-wide curriculum.